2019
DOI: 10.1186/s12889-019-7745-6
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a new measure to assess modern screen time in adults

Abstract: BackgroundScreen time among adults represents a continuing and growing problem in relation to health behaviors and health outcomes. However, no instrument currently exists in the literature that quantifies the use of modern screen-based devices. The primary purpose of this study was to develop and assess the reliability of a new screen time questionnaire, an instrument designed to quantify use of multiple popular screen-based devices among the US population.MethodsAn 18-item screen-time questionnaire was creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 32 publications
(33 reference statements)
0
53
0
2
Order By: Relevance
“…While some screen time was not measured in our study, we focussed on leisure-based television and computer use and driving as these behaviours may be more amendable due to modifications to the neighbourhood built environment. Notably, some recent evidence suggests that self-reported time spent using smartphones and tablets may be less reliable than self-reported television and computer time (Vizcaino et al 2019). Future studies can investigate environmental correlates of other types of sedentary behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…While some screen time was not measured in our study, we focussed on leisure-based television and computer use and driving as these behaviours may be more amendable due to modifications to the neighbourhood built environment. Notably, some recent evidence suggests that self-reported time spent using smartphones and tablets may be less reliable than self-reported television and computer time (Vizcaino et al 2019). Future studies can investigate environmental correlates of other types of sedentary behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…For a more detailed description of this 18-item questionnaire please see Vizcaino et al [15] The questionnaire has previously shown fair to excellent reliability, as assessed through intra-class correlation coefficients (ICCs = 0.50-0.90), and thus can be used to appropriately classify individuals into different screen time use categories (e.g. low vs. high) [15]. In addition, we explored the new phenomenon of binge-watching [16][17][18] by including the question "How often do you watch multiple episodes of a television program through digital streaming in a single sitting?"…”
Section: Screen Timementioning
confidence: 99%
“…Only recently has research begun to explore patterns of modern screen use across devices, times of day, and days of the week [15]. This approach to examining screen use represents an important next step in screen time research related to health.…”
Section: Introductionmentioning
confidence: 99%
“…However, contact with nature has been decreasing as more people live in urban areas and spend the majority of their time indoors [ 12 ]. The problem is further compounded by excessive time spent in front of a screen, a behavior that is increasing, especially among young adults [ 13 ]. Furthermore, young adults, particularly college students, experience a plethora of stressors that cause distress in their lives.…”
Section: Introductionmentioning
confidence: 99%